Transformation Employee Performance During Leadership Motivation Effect Over Kansai Prakarsa Coatings Company - Nastohar Nastohar; Rina Anindita (Journal of Multidisciplinary Academic, 2019)
This study aimed to analyse the transformation leadership style on employee performance case study motivation mediation over Kansai Prakarsa Coatings company. In this study, we used descriptive method to analyse the transformation over all division staffs working in the Kansai Prakarsa Coatings company with sampling technique using non probability sampling over 205 data observations. The Structural Equation Model (SEM) with LISREL are proposed in this study to obtain non probability sampling. The result shows transformation leadership style gives positive impact and significant influence to employee performance. The Motivation work also significant increased to employee performance over this company. The dimension of transformation leadership needs more attention to execute leadership orders and discipline work. The motivation needs to improve attention from the leadership to employees feel satisfied and have a good performance. This method is recommended to train staff at the leadership level to design transformation leadership models and increase employee motivation in near future.